Pelatihan Pembuatan Pupuk Kompos, Biopestisida, dan Bioherbisida sebagai Upaya Revitalisasi Pertanian Berkelanjutan di Desa Ngadireso, Malang - Maulana Arham; Muhammad Ikhwan Ramadhan; Nurul Rahma Khaerunisa; Markus Amartya Sam Hutahaean; Hemas Aulia Fazzahra; Kinaya Aliqa Wijaya; Resta Maryamzahra; Gathan Ferbiansyah Kusworo; Syaefudin (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Ngadireso Village has significant agricultural potential, particularly in cultivating horticultural commodities such as cabbage, chili, and oranges, which serve as the main sources of livelihood for the local community. However, agricultural practices in Ngadireso Village are still largely dominated by the use of chemical-based fertilizers, pesticides, and herbicides that pose risks to human health and the environment, while also increasing production costs. The community service activity conducted in Ngadireso Village aimed to enhance public understanding of the production of compost fertilizer, natural biopesticides, and bioherbicides that are more environmentally friendly, easy to make, and cost-effective. The methods used included socialization, demonstration of the production process, and hands-on practice with the Sri Rahayu 1 farmer group in Ngadireso Village. The materials used were locally sourced and easily obtainable within the village area. The results of the activity showed that the community was highly enthusiastic in participating in the training and gained a better understanding of the importance of sustainable agriculture. In addition to reducing dependency on synthetic chemicals, this activity also encouraged the utilization of local waste and promoted farmers’ self-reliance. It is expected that through this initiative, the people of Ngadireso Village will continue to develop a healthier, more economical, and environmentally conscious agricultural system.